Extradural Synovial Cyst of the Cervical Spine in a Saint Bernard - Ferrarin, Dênis Antonio; Polidoro Neto, Dakir Nilton; Schwab, Marcelo Luís; Ripplinger, Angel; Wrzesinski, Mathias Reginatto; Rauber, Júlia da Silva; da Silva, Marcia Cristina; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2021)
Background: Extradural synovial cysts (ESC) originate from an extrusion of the synovium in unstable or degenerated joints. In the spine, this condition can cause neurological signs such as hyperesthesia, proprioceptive ataxia and paresis. Since extradural presentations of synovial cysts are unusual in dogs, the aim of this manuscript is to report a case of extradural synovial cyst of the cervical spine, as well as the clinical findings, diagnosis, surgical treatment and clinical evolution after therapy. Case: A 3-year-old spayed Saint Bernard weighing 60 kg was presented to a Veterinary Medical Teaching Hospital with a history of acute paraparesis that evolved to non-ambulatory tetraparesis five days after the appearance of the first clinical signs. Neurological examination revealed non-ambulatory tetraparesis, normal muscle tone and segmental spinal reflexes in the thoracic and pelvic limbs, as well as cervical pain associated with limited neck movement. According to the neurological examination, the likely lesion location was the C1-C5 spinal cord segment. The differential diagnosis list included intervertebral disc disease, caudal cervical spondylomyelopathy, neoplasm, infectious or noninfectious inflammatory disease, and cystic diseases. Complete blood (cell) count and serum biochemistry tests were within reference limits. The cerebrospinal fluid analysis revealed 35 mg/dL of protein (< 30 mg/dL) and 27 cells (up to 5 cells/mm3) with a predominance of lymphocytes. In plain radiography, bone proliferations of the C4 (caudal) C5 (cranial) articular processes were observed and, in myelography, extradural spinal cord compression was evident between C4-C5 on the right side. The animal underwent dorsal laminectomy for spinal cord decompression. An extradural synovial cyst and proliferated articular processes were removed. At 1,281 days after surgery, the dog was clinically normal and presented no neurological deficits. Discussion: The etiology of synovial cysts has not been well established. However, it is believed that osteoarthritic degeneration associated with joint mobility could cause a rupture in the articular capsule, leading to a synovial membrane protrusion, which would fill with synovial fluid and compress spinal structures. ESC in the cervical region have been reported, often associated with cervical neoplasm. The case we report had no evidence of bone or intervertebral disc compression in myelographic and radiographic exams, abnormalities that would appear in cervical neoplasm. The patient underwent dorsal laminectomy to confirm the presumptive diagnosis and decompress the spine. In the histopathological exam, the cystic material consisted of connective fibrous tissue with a synovial cell lining layer, compatible with synovial cysts. The fluid drained during surgery was also analyzed, showing similarities to synovial fluid drained from other conventional joints. Cerebrospinal fluid analysis revealed mononuclear pleocytosis, a common finding in ESC. The ESC should be included in the differential diagnosis of dogs with cervical myelopathy, especially in young animals and large breeds. A myelographic exam is an important but not definitive auxiliary tool for diagnosis and the therapeutic plan. Dorsal laminectomy is an effective technique for treating ESC.